Avaliação do desenvolvimento de biofilme em meio suporte esponjoso em reator biológico de leito móvel (MBBR) no tratamento de efluente de indústria de celulose - Melchiors, Emeline (2019)
Brazil is the second-largest pulp producer in the world and, therefore, the tree sector is of great importance to the national economy. However, these industries are in sixth place in terms of environmental pollution, being responsible for disposing of effluents with high polluting potential if not properly treated. Most pulp mill industries use biological treatments. The moving bed biofilm reactor (MBBR) has been gaining popularity due to its stability, compact size, removal efficiencies, and low sludge production. This system allows the growth of adhered biomass (biofilm) in supports. The supports, also called carriers, move throughout the reactor volume with the aid of aeration. This study evaluated the performance of the Aquaporousgel (APG), a functional sponge developed by the Japanese company Nisshinbo Chemical Inc., used in an MBBR to treat pulp mill effluent. An MBBR system in a laboratory-scale with utile volume of 1 L was filled by this innovating sponge carrier to treat effluent from a pulp industry. The MBBR-APG operated continuously for 240 d with an organic load rate (OLR) of 0.6 and 1.2 kgDQO m-3 d-1, resulting in hydraulic retention times (HRT) ranging from 1.0 to 2.7 days. The treatment efficiency was determined by the removal of chemical oxygen demand (COD), biochemical oxygen demand (BOD5), total organic carbon (TOC), color, turbidity, total phenolic compounds, lignin derivatives, and fluorescence excitation-emission matrix. Biofilm development was evaluated by quantifying adhered solids, scanning electron microscopy (SEM), and microbiological analyses. The MBBR-APG presented a better performance at OLR of 1.2 kgDQO m-3 d1, achieving average organic matter removals of 62.7, 48.4 and 55.7% for BOD5, COD and TOC, respectively. Despite that, the biological treatment generated increments of other fluorogenic compounds. The hypothesis of this phenomenon is the result of the action of anaerobic microorganisms present in anoxic microzones formed in the inner of the sponge carrier due to the difficulty in oxygen diffusion. The SEM analysis indicated that the APG sponge has a functional structure better than the traditional polyurethane sponges. It is possible to observe the development of a biofilm matrix composed of extracellular polymeric substances (EPS) and the presence of fungi and bacteria. Microbiological analyses confirmed the presence of fungi genus Aspergillus and Trichoderma, and bacterial genus Bacillus sp., Serratia sp. And Lysibacillus sp. This study presented important contributions to the use of sponge carrier, compounds biotransformation in biological treatments of pulp effluents, and the development of biofilm matrix in these systems.